Investigating the contribution of geometrical parameters and immersion time on fracture toughness of jute fabric composites using statistical techniques (Fracture and Structural Integrity, 2018)
The aim of this work is to evaluate the failure analysis of jute fabric reinforced composite using statistical technique for marine applications. A fracture mechanics approach is proposed to determine the failure load and fracture toughness of the composite. Jute fiber reinforced epoxy composites were fabricated by hand lay-up technique. The polymer composite is intended for marine applications as an alternative material, mainly in high moisture environments. Thus an investigation was conducted to evaluate the fracture mechanic parameter by immersing composite specimens in sea water. The statistical method of Taguchi was used for experimental design. Edge Notched Tension (ENT) and Single Edge Notched Bend (SENB) test were conducted according to the ASTM E1922 and ASTM D5045 respectively. Main effect graphs are obtained to study the effect of a/w (Crack length to width ratio), thickness and immersion time of composite on fracture mechanics parameters. The approach of calculating the percentage of contribution of control factors was established using by analysis of variance (ANOVA).  The influence of fracture parameters of control factors can be analysed by using 3-D response surface graph (RSM). The Validation of experimental results for fracture parameters agreed well with the predicted values.
Keywords: Polymer composites; Natural fiber; Fracture toughness; Taguchi; ANOVA; RSM